Isolation, quantification and formulation of bioactive peptides (Adipokines) for diabetes and obesity from adipose tissue in halal meat - Khattak, Muhammad Muzaffar Ali Khan; Abdul Rahman, Suzanah; Md Isa, Muhammad Lokman; Syed Osman Idid, Syed Zahir Idid; Md. Aris, Mohd. Aznan; Bakhtiar, Muhammad Taher; Phang, Ing Chia (2017)
Background: Given the beneficial roles of adiponectin on body metabolism and its profound protective effects against metabolic disease, a better understanding of the adiponectin secretion and regulation is very important. Objectives: The objective of this study was to isolate, detect, quantify the total adiponectin in trimmed off abdominal adipose tissues from halal meat sources namely chicken, beef and lamb and tested on STZ-induced diabetic rats. Methods: Abdominal adipose tissues were isolated from the aforementioned sources and delipidation of the tissues were performed by chloroform/methanol extractions. Afterwards, the protein concentration was determined by using Protein Assay Bicinchoninate Kit method. This was followed by quantification of the adiponectin using ELISA assay kit. Then continue with tested in STZ-induced diabetic rats on blood glucose and blood lipid, hormone measurement and lastly quantification of PPAR-α mRNA, AMPK mRNA, AdipoR1 mRNA, AdipoR2 mRNA and AdipoQ mRNA in the hepatocytes. The experiment was conducted in triplicates and the results are presented as means ± SD. The data was statistically analyzed by using SPSS (Version 21.0). One-way analysis of variance (ANOVA) was used and the data was considered statistically different at 95% confidence interval. Results: Results indicate that the extraction of 10 gram subcutaneous adipose tissues from chicken, beef and lamb yielded 0.10 gram, 0.15 gram and 0.15 gram respectively of protein amount which was 1 - 1.5 % from total tissue mass. The protein concentration in abdominal adipose tissue from chicken, beef and lamb were 1.25 ± 0.05, 1.75 ± 0.05 & 2.53 ± 0.07 mg/ml, respectively. The isolated adiponectin concentration in chicken, beef and lamb were 158 ng/ml± 0.05, 24 ± 0.05µg/ml and 37 ± 0.08 ng/ml, respectively. Adiponectin concentration in beef abdominal adipose tissue significantly (P<0.05) higher compared to chicken and lamb. In animal study, the normal, insulin-treated, PCCA-treated (protein containing chicken adiponectin), PCBA-treated (protein containing beef adiponectin) and PCLA-treated (protein containing lamb adiponectin) diabetic groups exhibited significantly (P<0.05) reduced blood glucose levels after the treatment period when compared with the control diabetic (no treatment) group. Then, there is no significant difference of blood cholesterol levels in between groups, however the normal, insulin-treated, PCBA-treated and PCLA-treated diabetic groups shows a reduction of cholesterol level at the end of the experimental period. Similarly, the normal, insulin-treated, PCBA-treated and PCLA-treated diabetic groups exhibited significantly (P<0.05) reduced triglycerides levels after the treatment period when compared to the control diabetic (no treatment) group. Moreover, serum adiponectin concentration was significantly (P<0.05) higher in the normal, insulin-treated, PCBA-treated, PCCA-treated and PCLA-treated diabetic groups compared to control diabetic (no treatment) group. Nevertheless, serum insulin concentration was only significantly (P<0.05) higher in normal and insulin-treated groups as compared to control diabetic (no treatment) group. Lastly, AMPK, AdipoR1 and AdipoR2 mRNAs was significantly (p<0.05) increased in the normal, insulin-treated, PCBA-treated, PCCA-treated and PCLA-treated diabetic groups compared to control diabetic (no treatment) group. Then, PPAR-α mRNA was only significant (p<0.05) for normal, insulin and PCCA-treated diabetic groups compared to control diabetic (no treatment) group. However, there is no significant different between groups for AdipoQ mRNA. Conclusion: The present study suggests that beef protein had the highest amount of adiponectin protein and gave highest positive effects on STZ-induced diabetic rats. Thus, Adiponectin proteins extracted from wasted adipose tissues in meat sources can be one of the promising target for future novel pharmacological and therapeutic treatment/prevention for insulin resistance and metabolic diseases.